Karakteristik Kandungan Kimia dan Komponen Bioaktif Rumput Laut Hijau Halimeda sp. Dari Kepulauan Seribu - Sujaka Nugraha; Humairani Humairani; Siti Balqis Huriyah; Eti Kurniawati (Jurnal FishtecH, 2022)
Halimeda sp is a green seaweed belonging to the order Bryopsidales, class Chlorophyta. Production data from the genus Halimeda sp in Indonesia yet has not been reported by   the Ministry of Fisheries and Marine Affairs because it belonged to the unknown type of potential. The purpose of this study was to determine the chemical and bioactive components of Halimeda green seaweed. The chemical components of seaweed       Halimeda sp included of moisture content, ash, protein, fat, and carbohydrates (by different). Analysis of bioactive components was carried out qualitatively and quantitatively by counted total phenol. The results showed that the proximate analysis of Halimeda sp contained 3.15% moisture content, 87.61% ash content, 0.2% protein content, 1% fat content, and 11.19% carbohydrate (by different) content. Qualitatively Halimeda sp positively contains steroid and alkaloid compounds and was negative for flavonoids, phenols, tannins, saponins, and triterpenoids. The quantitative analysis of the total phenol content of Halimeda sp. extracted with 99.9% ethanol solvent was 273.88 mg GAE/g.